Tekstil endüstrisi boyama atıksularının karakterizasyonu ve biyolojik arıtılabilirliği - Yapraklı, Berna (Fen Bilimleri Enstitüsü, 1997)
Bu çalışmada tekstil atıksularında yeni bir altkategorizasyon yaklaşımı için geliştirilen matris formatına işlerlik kazandırmak amacı ile matris bileşenlerinden üçü ele alınarak, biyolojik antılabilirlik açısından önem taşıyan, çözünmüş inert (kalıcı) organik madde (Sı), partiküler inert (kalıcı) organik madde (Xı), kolay ayrışabilir organik madde (Ss) ve yavaş ayrışabilir organik madde (Xs) içeriğinin belirlenmesi ve kinetik ve stokiometrik katsayıların bulunması amacıyla bir dizi deneysel çalışma yürütülmüştür. Birinci bölümde, çalışmanın anlam ve önemi, amaç ve kapsamı kısaca belirtilmiştir. İkinci bölümde, tekstil endüstrisi atıksularındaki altkategoriler farklı yaklaşımlarla ele alınmış ve bu altkategorilere ait atıksu kaynakları, atıksu miktar ve karakterizasyonları ve yeni altkategorizasyon yaklaşımı üzerinde durulmuştur. Üçüncü bölümde, biyolojik arıtma kinetiği, aktif çamur prosesi incelenmiş, atıksulardaki KOİ bileşenleri (Ss ve Xs) ve kinetik ve stokiometrik katsayıların belirlenmesi yöntemleri anlatılmıştır. Dördüncü bölümde incelenen atıksu numunelerinin konvansiyonel ve biyolojik bazlı atıksu karakterizasyonu ile kinetik ve stokiometrik katsayıları tablolar halinde sunulmuştur. Ayrıca bu bölümde deneylerin planlanması ve laboratuar çalışmalarıda ele alınmıştır. Beşinci yani son bolünde tüm çalışma genel olarak değerlendirilmiştir.

The textile industry is one of the most important and common industry for many developed and developing countries, because of its impact on the environment. Textile industry has a very complex nature in terms of raw materials used, techniques employed, chemical applied and products. Different techniques and a variety of operations and processes are involved within this industry. Because of the dynamic structure of the industry, it is meaningless to speak of a typical textile effluent. The amount of wastewater and its quality in plants show a wide range of values. It is not practicable to attempt to explain the differences between effluents from different sources without reference to the essential characteristics of the effluent-producing process in this industry. Industrial pollution control calls for a systematic evaluation based on pollutional characteristics, treatability tests and actual treatment performance data leading to a proper characterization, treatment technology and to rational discharge standards. Despite an abundance of related data, this systematic approach can hardly be considered adequately defined for the textile processing industry, mainly because the subcategorization criteria are not identified in adequate detail due to the complexity of the problem. It is difficult to get healthy results with the subcategorization now in use. The purpose of the subcategorization is to find the differences defined in the wastewater of the plants which use different process in the production of the same products and have same production differentiation's. An example matrix which will be used as a basis for pollution evaluations including type of the fiber dyed, dyes used, physical forms dyed, operation type and dyeing equipment used is developed for the textile dyeing processes. Biological treatment systems are commonly used in the treatment of textile industry wastewaters. Activated sludge system is the most popular biological treatment system for the textile industry wastewaters. Activated sludge systems are based on the concept that organics in the wastewater are biologically depleted by microorganisms and removed in this way under the aerobic conditions. xv Activated sludge theory was based on the concept that effluent substrate concentration is not depend on influent substrate concentration and influent and effluent concentrations have the same characteristics. The identification of influent characteristics with regard to the organic content is useful from the standpoint of process kinetics and therefore in treatment. The organic matter content measurements of the wastewaters containing complex organic substances are based on collective parameters such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), total organic carbon (TOC), since it is not possible to measure these matters individually. One of the most common collective parameter for the identification of influent characteristics is the chemical oxygen demand (COD). Chemical oxygen demand is appeared to be a more useful parameter than biochemical oxygen demand (BOD).. For modeling and design of biological treatment processes, we need reliable and important information that obtained from wastewater characterization. The wastewater characterization mainly cover fractionation of the chemical oxygen demand (COD) and determination of significant kinetic and stoichiometric coefficients. COD fraction includes inert COD and biodegradable COD together. The inert COD fraction subdivides into soluble inert COD (Si) and particulate inert COD (Xi). The biochemical reactions in the reactor do not effect the soluble inert COD but the particulate COD accumulate in the activated sludge. The components of biodegradable COD are readily biodegradable COD (Ss) and slowly biodegradable COD (Xs). Mathematical models and experimental methods determine the COD fractions and define the biological treatment so they should find consistent and reliable values together. Wastewaters usually contain a very wide spectrum of organics with respect to biodegradability. The initial soluble inert COD fraction passes through the activated sludge systems in an unchanged form. This fraction, not critical in conventional wastes, becomes significant in industrial effluents and especially in strong wastes since it leads to misinterpretation of biological treatability results; it also makes it difficult to meet effluent limitation criteria expressed in terms of COD for a number of industrial categories. Incorrect results are reached due to the interference of soluble inert metabolic products on the initial soluble inert COD, the target of the measurement. In activated sludge systems the microbial inert product fraction in the effluent stream can be minimized by making proper adjustments in the design and operational conditions. Whereas the influent and effluent soluble inert wastewater concentration remain the same. Thus, it is important to determine the initial inert soluble COD fraction of wastewater correctly. xvi The treatability of wastes incorporated in the study is relates to two different concepts. The first concept is inert COD fraction; the determination of the readily biodegradable COD, Ss, the determination of the slowly biodegradable COD, Xs. The other concept is the kinetics of the degradable components and it is reflected by the kinetic constants, namely maximum specific growth rate, //, the heterotrophs yield coefficient, Yh, endogenous decay rate, bn. These parameters and constants have been determined by batch test reactors and respirometric techniques that enable the experimental assessment. The Inert COD Fraction Various methods are proposed to define the influent soluble COD component. The readily biodegradable substrate is exhausted directly by the heterotrophs and the heterotrophs use it for growth of the biomass. The slowly biodegradable substrate is changed to the readily biodegradable substrate by hydrolyzed for using. The soluble inert organic matter is consist of the soluble inert organic matter (Si) and the soluble microbial products (Sp) of the wastewater. The soluble microbial products construction has not been understood completely. The experiment requires two aerated batch reactors, one of them is filtered wastewater reactor, and the other one is unfiltered wastewater reactor. In both reactors the total and soluble COD are monitored for an enough period for determination of the biodegradable substrate is ended. After this period the reactors have only initial inert COD and residual products. Each reactor has include minimum biomass concentration which acclimated to the wastewater before the experiment. The appropriate F/M (substrate to biomass) ratio is l.OgCOD/gVSS.day and the amount of the biomass concentration for the acclimation is between 10-50 mg/lt. The other method for determination of S| and Xi is also has three aerobic batch reactors of unfiltered wastewater, filtered wastewater and glucose. All the reactors have include minimum biomass concentration which acclimated to the glucose-wastewater mixture. The same periods are monitored like the other method. At the end of the experiment when all biodegradable substrates in the three reactors are decreased, the differences between the residual COD levels between filtered and glucose reactors give the initial inert COD. The Readily Biodegradable COD (Ss) Regarding, the application of the model in design most of the constant values can be accepted as adequate, however there are some that are dependent on influent characteristics or on process configuration and load patterns that preferably should be determined for each wastewaters : constants dependent on the influent characteristics are the COD fractions, and the maximum growth rate for the nitrifiers; one constant that is xvii dependent on the process configuration and load pattern is the maximum growth rate of the heterotrophs. Knowledge of the influent COD fractions is of primary importance in determining oxygen demand, sludge wastage, denitrification capacity of excess biological P removal, and the relative magnitudes of the fractions can differ greatly between wastewaters. The readily biodegradable COD concentration (Ss) is very important for heterotrophic growth. The method for determination of Ss is like this; in this experiment a selected volume of wastewater of known total COD concentration is mixed with minimum biomass concentration in aerobic batch reactor. After mixing, the OUR is measured approximately every 5 to 10 minutes for about 4 to 5 hours. With correct selection of the F/M ratio ( food to microorganism ), the OUR from start of the experiment remains constant for a period of 1 to 3 hours depending on the readily biodegradable COD fraction, whereafter the OUR decreases fairly rapidly and levels off at a second plateau level. The initial high OUR is a consequence of the utilization of the readily biodegradable COD from the wastewater as well as that derived from hydrolysis of the particulate biodegradable COD. Once the readily biodegradable COD from the influent is depleted, the OUR rapidly drops to the second plateau level, which is the rate associated with the utilization of the readily biodegradable COD generated by hydrolysis of the particulate biodegradable COD. The Slowly Biodegradable COD ( Xs) In wastewater the main part of the biodegradable COD is slowly biodegradable COD. Because of this, to identify the slowly biodegradable part of the COD, is very important. The slowly biodegradable COD is transformed into readily biodegradable COD by hydrolysis and it is used in heterotrophs growth. The slowly biodegradable COD ( Xs) affect oxygen respiration only if growth is limited by substrate and therefore respiration is dominated by hydrolysed substrate. Influent wastewater includes soluble and particulate organic matters; Cti = Ssi + Xsi Filtered wastewater only includes soluble components; Sti = Ssi + Shi + Sn With this two equations the slowly biodegradable organic matter components will be find. xvui Maximum Specific Growth Rate ( // ) The procedure proposed by KAPPLER and GUJER (1992) is followed; endogenous decay model is used in this procedure and in this experiment a known COD concentration of filtered wastewater is mixed with minimum biomass concentration in an aerobic batch reactor. The appropriate biomass concentration is depend on the readily biodegradable COD concentration of wastewater. At the beginning of the experiment the heterotrophic growth is very fast because of the readily biodegradable COD. The microorganism concentration is minimum so the increasing OUR values can be seen. When the readily biodegradable COD is ended, the heterotrophic growth continues with the hydrolysis substrate in this respect the OUR values slow down with the hydrolysis rate. During the first period of the batch - test, oxygen respiration increases due to the unlimited heterotrophic growth. Suddenly oxygen uptake rate decrease because of limiting concentrations of readily biodegradable substrate, Ss, to a lower level. At this level oxygen respiration is dominated by growth on substrate, which is released by hydrolysis. The slope of the OUR profile yields the value of (//-bH).t on the basis of the following equation: OUR / x ln7^-=^-bH) Heterotrophic Yield Coefficient ( Yh ) Heterotrophic yield coefficient, YH, is an important parameter for activated sludge modeling. Because to calculate the right sludge production and oxygen demand, the heterotrophic yield coefficient is needed. According to the procedure used in this study; if OUR and soluble COD are measured at the same time in the samples taking from the aerobic batch reactors, yield coefficient YH obtained from OUR and soluble COD profile gives following equation: AO+AO' Y, = 1 ACODsolublc AO, is the area difference between two oxygen levels and AO1, is the oxygen consumption because of Sh. The Endogenous Decay Rate ( bn) The method to calculate bH involves plotting the change of OUR with time in a batch reactor that is not abandoned of substrate. In this test temperature do not effect bn. The OUR is measured two times every day for about 8 - 10 days. The slope of the OUR profile that draw with the following equation gives the value of bH. xix In OUR = In [ 1.42 ( 1 - fE). bH. XH ] - bH. t The Runge - Kutta numerical analysis method has been used for the solution of the differential equations to give the kinetic coefficients; ks, kh, kx for the general discharge experiment.
Characterization and biological treatability of textile dyeing wastewaters
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1997
Keywords: Biyolojik arıtma; Endüstriyel atık su; Tekstil endüstrisi; Biological treatment; Industrial waste water; Textile industry